Increased transfusion‐free survival following auxiliary pig liver xenotransplantation. (1st August 2014) - Yeh, Heidi; Machaidze, Zurab; Wamala, Isaac; Fraser, James W.; Navarro‐Alvarez, Nalu; Kim, Karen; Schuetz, Christian; Shi, Shuai; Zhu, Alexander; Hertl, Martin; Elias, Nahel; Farkash, Evan A.; et al.
Abstract Background Pig to baboon liver xenotransplantation typically results in severe thrombocytopenia and coagulation disturbances, culminating in death from hemorrhage within 9 days, in spite of continuous transfusions. We studied the contribution of anticoagulant production and clotting pathway deficiencies to fatal bleeding in baboon recipients of porcine livers. Methods By transplanting liver xenografts from α1, 3‐galactosyltransferase gene‐knockout (GalT‐KO) miniature swine donors into baboons as auxiliary organs, leaving the native liver in place, we provided the full spectrum of primate clotting factors and allowed in vivo mixing of porcine and primate coagulation systems. Results Recipients of auxiliary liver xenografts develop severe thrombocytopenia, comparable to recipients of conventional orthotopic liver xenografts and consistent with hepatic xenograft sequestration. However, baboons with both pig and native livers do not exhibit clinical signs of bleeding and maintain stable blood counts without transfusion for up to 8 consecutive days post‐transplantation. Instead, recipients of auxiliary liver xenografts undergo graft failure or die of sepsis, associated with thrombotic microangiopathy in the xenograft, but not the native liver. Conclusion Our data indicate that massive hemorrhage in the setting of liver xenotransplantation might be avoided by supplementation with primate clotting components. However, coagulation competent hepatic xenograft recipients may be predisposed to graft loss related to small vessel thrombosis and ischemic necrosis.